THE SPECIFIC NATURE OF SAKKOKIY’S DIVAN - Abdukhalikova, Maftuna (International Conference on Science, Education & Law, 2026)
This article analyzes the lexical features of the Divan of Sakkokiy, one of the prominent representatives of classical Uzbek literature. The artistic and aesthetic significance of the poet’s творчество, as well as the usage of lexemes belonging to Turkic, Persian, and Arabic lexical layers within the Divan, are examined. The study highlights methods of word formation, particularly the linguistic nature of derivative words formed through affixation, based on textual examples. Furthermore, the article reveals the specific characteristics of figurative devices, izofa constructions, and lexical units related to thematic groups found in the Divan. The findings demonstrate that Sakkokiy’s Divan serves as an important source for the study of the historical lexicology of the Uzbek language.